2011
DOI: 10.1063/1.3589371
|View full text |Cite
|
Sign up to set email alerts
|

Trap-limited and percolation conduction mechanisms in amorphous oxide semiconductor thin film transistors

Abstract: The electron conduction mechanism in the above-threshold regime in amorphous oxide semiconductor thin film transistors is shown to be controlled by percolation and trap-limited conduction. The band tail state slope controls the field effect mobility, while the average spatial coherence length and potential fluctuation control percolation conduction. In these limits, the field effect mobility is found to follow a power law, from which a universal mobility versus carrier concentration dependence is extracted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
212
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(227 citation statements)
references
References 17 publications
15
212
0
Order By: Relevance
“…As expected, structural disorder increases with the substitution level in ternary and quaternary AOSs; however, there is no clear understanding regarding the role played by the individual metal species in the formation of amorphous state and the AOSs properties. Most research has focused on quaternary oxides such as a-In-Ga-Zn-O or a-Zn-In-Sn-O given their technological appeal; [48,49,[51][52][53][54][55][56][57][62][63][64][65][66]68,69,73,74,76] only a few studies addressed the properties of ternary AOSs systematically. [67,85,86] Moreover, a comparison of the results available in the literature is likely to be inconclusive because the crystallization temperature depends strongly not only on the metal composition but also on growth conditions (such as oxygen partial pressure, postdeposition temperatures and times) as well as film thickness.…”
Section: Local Structure and Amorphization Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, structural disorder increases with the substitution level in ternary and quaternary AOSs; however, there is no clear understanding regarding the role played by the individual metal species in the formation of amorphous state and the AOSs properties. Most research has focused on quaternary oxides such as a-In-Ga-Zn-O or a-Zn-In-Sn-O given their technological appeal; [48,49,[51][52][53][54][55][56][57][62][63][64][65][66]68,69,73,74,76] only a few studies addressed the properties of ternary AOSs systematically. [67,85,86] Moreover, a comparison of the results available in the literature is likely to be inconclusive because the crystallization temperature depends strongly not only on the metal composition but also on growth conditions (such as oxygen partial pressure, postdeposition temperatures and times) as well as film thickness.…”
Section: Local Structure and Amorphization Efficiencymentioning
confidence: 99%
“…The research area of transparent conducting oxides (TCOs) dates back to 1907 when CdO was reported to combine both optical transparency in the visible range and good electrical of amorphous indium oxide appeared in 2009, [61] followed by models of electron transport in multi-cation AOSs, [62][63][64][65][66][67] DFT calculations of defect formation, [68][69][70][71][72][73][74][75] and statistical descriptions of amorphous network. [76][77][78] However, several key questions regarding the nanostructure and morphology, crystallization, carrier generation, and conductivity mechanisms in AOSs remain unanswered and require a unified theoretical framework capable of handling all these aspects in tandem.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-film transistors are good examples: the mobility is affected by band tailing [2], although the band-tail-state effect on carrier transport is strongly material dependent [3]. Band tails are also known to reduce the efficiency of solar cells [4,5] and to be the limiting factor in the case of amorphous Si solar cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…22 The electron conduction in a-IGZO is proposed by percolation conduction theory, where the electrons need to pass through the Gaussian distribution of energy barriers with an average barrier height of 50meV. 21,23 These barriers are originated by the disorder of Ga + /Zn + cations, which make the Gaussian type distribution around E C in amorphous IGZO. 21 The negative temperature coefficient of µ sat observed for positive V TG (shown in Fig.…”
Section: -4mentioning
confidence: 99%